Desenvolvimento anatômico dos órgãos vegetativos do feijão (Phaseolus vulgaris L.): II. Ápice radicular - Monteiro da Silva, Eldo Antônio (Revista Ceres, 2025)
The bean (Phaseolus vulgaris L.) Bush Lake 290' root apex is cited as having an open system. Various regions of initial cells may be observed: a collumela and cortical initials that give rise respectively to the root cap, cortex and epidermis; and a central zone of initial cells that initiates the stele. Periclinal divisions of the presumptive endodermis initiate the cortical cells.